Safety and immunogenicity of an Ad26.ZEBOV booster dose in children previously vaccinated with the two-dose heterologous Ad26.ZEBOV and MVA-BN-Filo Ebola vaccine regimen: an open-label, non-randomised, phase 2 trial. Issue 3 (March 2023) - Manno, Daniela; Bangura, Agnes; Baiden, Frank; Kamara, Abu Bakarr; Ayieko, Philip; Kallon, Joseph; Foster, Julie; Conteh, Musa; Connor, Nicholas Edward; Koroma, Bockarie; Njie, Yusupha; Borboh, Paul; et al.
Summary: Background: Children account for a substantial proportion of cases and deaths during Ebola virus disease outbreaks. We aimed to evaluate the safety and immunogenicity of a booster dose of the Ad26.ZEBOV vaccine in children who had been vaccinated with a two-dose regimen comprising Ad26.ZEBOV as dose one and MVA-BN-Filo as dose two. Methods: We conducted an open-label, non-randomised, phase 2 trial at one clinic in Kambia Town, Sierra Leone. Healthy children, excluding pregnant or breastfeeding girls, who had received the Ad26.ZEBOV and MVA-BN-Filo vaccine regimen in a previous study, and were aged 1–11 years at the time of their first vaccine dose, received an intramuscular injection of Ad26.ZEBOV (5 × 10 10 viral particles) and were followed up for 28 days. Primary outcomes were safety (measured by adverse events) and immunogenicity (measured by Ebola virus glycoprotein-specific IgG binding antibody geometric mean concentration) of the booster vaccine dose. Safety was assessed in all participants who received the booster vaccination; immunogenicity was assessed in all participants who received the booster vaccination, had at least one evaluable sample after the booster, and had no major protocol deviations that could have influenced the immune response. This trial is registered with ClinicalTrials.gov, NCT04711356 . Findings: Between July 8 and Aug 18, 2021, 58 children were assessed for eligibility and 50 (27 aged 4–7 years and 23 aged 9–15 years) were enrolled and received an Ad26.ZEBOV booster vaccination, more than 3 years after receiving dose one of the Ad26.ZEBOV and MVA-BN-Filo vaccine regimen. The booster was well tolerated. The most common solicited local adverse event during the 7 days after vaccination was injection site pain, reported in 18 (36%, 95% CI 23–51) of 50 participants. The most common solicited systemic adverse event during the 7 days after vaccination was headache, reported in 11 (22%, 12–36) of 50 participants. Malaria was the most common unsolicited adverse event during the 28 days after vaccination, reported in 25 (50%, 36–64) of 50 participants. No serious adverse events were observed during the study period. 7 days after vaccination, the Ebola virus glycoprotein-specific IgG binding antibody geometric mean concentration was 28 561 ELISA units per mL (95% CI 20 255–40 272), which was 44 times higher than the geometric mean concentration before the booster dose. 21 days after vaccination, the geometric mean concentration reached 64 690 ELISA units per mL (95% CI 48 356–86 541), which was 101 times higher than the geometric mean concentration before the booster dose. Interpretation: A booster dose of Ad26.ZEBOV in children who had received the two-dose Ad26.ZEBOV and MVA-BN-Filo vaccine regimen more than 3 years earlier was well tolerated and induced a rapid and robust increase in binding antibodies against Ebola virus. These findings could inform Ebola vaccination strategies in paediatric populations. Funding: Innovative Medicines Initiative 2 Joint Undertaking. Translation: For the French translation of the abstract see Supplementary Materials section.